School Principal’s Leadership Style and Teachers’ Job Performance: A Systematic Review of Literature - Ortiz, Coulyn; De Jesus, Leonora (Journal of Interdisciplinary Perspectives, 2024)
The leadership style of the school principal plays a vital role in an institution because its primary goal is to guide, motivate, direct, and influence the school community—which includes teachers, staff, and other stakeholders—to fulfill the institution's vision, mission, and goals. As a result, the researcher conducted this systematic literature review to identify the effective leadership styles of school principals and how they connect to teachers' job performance, as successful teachers can transform an institution. The researcher thoroughly reviewed twenty (20) research articles, and the results revealed that the school principal uses a variety of leadership styles. Three of these—democratic, transformational, and autocratic—show potential and positively correlate with teachers' job performance. However, using an authoritarian leadership style should be conducted cautiously by the school principal as it can decrease teachers' job performance if not properly practiced. Furthermore, it has been concluded from the studied researchers that certain leadership styles have no substantial association, or a negative relationship, with teachers' job performance. Therefore, the authors of the reviewed literature did not recommend that school principals use it in their leadership roles within an institution.